Stylistic features of Cyrillic graffiti of the pre-Mongol period in Kyiv St. Sophia’s Cathedral - Dyadyshcheva-Rosovetska, Julia (Current issues of Ukrainian linguistics: theory and practice, 2018)
The article examines the peculiarity of the concept of the linguistic style of the literature of Kyiv Rus, which is closely linked with the traditions of the scientific study of this very “red writing”. The specificity of Old Russian literature as medieval leads to its almost church character, and the specific "simplicity" in the structure of secular literary works of its own, such as "The Word of the Igor’s Regiment," forcing researchers to engage in secular business texts, for example, the chronicles that are works of historical the genre. That is, in this case, the peculiarity of the concept of literary language reflecting the peculiarity of the notion of ancient Russian literature, which is by no means the "artistic" literature of the modern type, or fiction. Accordingly, the volume of materials that should serve to study the stylistics of literature of the Kiev Rus era is determined by the peculiarity of scientific ideas about the very literature itself and about the literary language in which it is created. These considerations make us propose as an auxiliary "meter" to study the style of literature of the Kiev Rus age the criterion of reflection or absence of certain poetics in the texts. As is well known, the phenomenon of poetics is legitimately extended to folklore, to contemporary business writing, and to non-folklore oral speech activity. Thus we get the opportunity to define in the same graffiti Kiev Saint Sophia’s Cathedral style of church writing and oral canon, folklore and business law. But with such an approach, the bright feature of the stylistics of graffiti Sofia of Kiev in the comparison with the volume similar to the volume of graffiti texts of Novgorod Saint Sofia Cathedral is immediately striking: among the Kiev graphite there is practically no folklore of origin, not to mention the reflection of the pagan rituals that we find on the walls of the Novgorod Saint Sofia Cathedral. This conclusion can be reliably based on statistical data. But when the researchers find in the texts of the XI–XIII centuries. syllabic or "elements of sillabotonism", it is worth reminding of the very probable chance of an appropriate combination of sounds and syllables. It is much more reliable to refer some graffiti to the clerical poem. But we must not forget the hypotheticalness of such identification in general, as well as the fact that only the adaptation of the Byzantine poem to the Slavic language context can be considered.